Nail Alterations in Cutaneous B-Cell Lymphoma With Extracutaneous Relapse - Mohagheghi, Fathollah; Anoushirvani, Ali Arash; Mohagheghi, Taher; MA, Daneshmand (Reports of Radiotherapy and Oncology, 2015)
Introduction: Cutaneous B-Cell lymphoma can be associated with clinically significant nail alterations, the presentation of which can be unusual and misleading. To date, only a few reports have demonstrated direct specific tumor infiltration of the nail bed with lymphoma, while there is much less information about infiltration of nail bed with diffuse large B-cell lymphoma. Case Presentation: We describe the case of a 74 years old man presenting with nail bed ulceration who developed clinically significant nail shape alterations. Light microscopy studies demonstrated the presence of a specific lymphocyte infiltrate within the nail bed. The IHC analysis demonstrated diffuse large B cell lymphoma (DLBCL). Conclusions: Specific nail involvement should be recognized and considered in all patients with cutaneous B-cell lymphomas specially when there is refractory to conventional treatment.